Caracterización de la perturbación psíquica en víctimas de lesiones personales (2020)
The term psychic disturbance in forensic science refers to a mental health condition within the context of harmful acts against the well protected of personal integrity, which significantly violates the individual's personal, family, social or occupational functionality. For this, the role played by structural lesions of the central nervous system as causes of this type of conditions must be carefully studied, and it is precisely in countries such as Colombia that it is one of the main causes of disability in the young population, producing cognitive and psychosocial alterations. emotional that can become permanent. Based on all this, it is sought not only to determine a clinical and forensic diagnosis of the case, but also to contribute and provide highly relevant information on these events that significantly impact the biopsychosocial well-being of the population contextualized in public policy. To do this, a meticulous review of the expert reports concluded on psychic disturbance between September 2012 and June 2017 was carried out in the southwestern region, Cali headquarters, of the National Institute of Legal Medicine and Forensic Sciences (INMLCF), for cases in which the crime of personal injury had been incurred and in whose results it was observed that 78.09% of the cases studied were reported positive for psychic disturbance regardless of its cause, of which 97.2% of these cases were permanent. Regarding the results obtained, in addition to exposing these overwhelming figures that indicate the worrying situation suffered by the victims in terms of psychic disturbance, it is also intended to contribute to the generation and implementation of public policies at the national level, through the routes of Comprehensive Health Care, which allows to adequately face this problem and thus progressively reduce both the incidence and the biopsychosocial impact that these events generate in the general population, especially in the young population, which is the most affected in this type of situation.